Clinical and Resistance Pattern of Coagulase Negative Staphylococci - Shaween Omed Faiq; Sherko Ali Omer (Advanced Medical Journal)
Background and Objectives: Coagulase-negative staphylococci are commensal bacteria inhabiting human. Isolation of these bacteria from healthcare-associated and community infections is increasingly observed with resistance response to many antibiotics. The study aimed to identify the clinical and antimicrobial resistance pattern of coagulase-negative staphylococci isolated from various healthcare-associated and community-acquired infections.